Detection of simultaneous structural problems using multiple structural health monitoring techniques - Yang, Lu (2017)
Civil infrastructures are built for long-term use spanning several decades. After the construction, cracks, wear and tear, fatigue, creep, etc., will appear anytime during their life span, which significantly affects the capacity of the structure to bear loads. Hence structure health monitoring (SHM) technique came into existence to detect the structural problems and increase its life span. However, the single SHM technique cannot solve simultaneous structural problems such as cracks - loads, static load - impact, etc. In this project, the author aims at integrating multiple existing SHM techniques such as electromechanical impedance (EMI), electrochemical analysis method, metamaterial based sensing technology, to detect different co- existing problems in the structure. Experiments such as detection of co-existing static and dynamic load on a 2D plate, tyre pressure and boundary monitoring, damages, their propagation were studied using these SHM techniques.